2005
DOI: 10.1093/jnci/dji241
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Black–White Differences in Receipt of Recommended Colon Cancer Treatment

Abstract: Black and white Medicare-insured colon cancer patients have an equal opportunity to learn about adjuvant chemotherapy from a medical oncologist but do not receive chemotherapy equally. Little disparity was explained by health systems; more was explained by illness severity, social support, and environment. Further qualitative research is needed to understand the factors that influence the lower receipt of chemotherapy by black patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
135
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(147 citation statements)
references
References 62 publications
9
135
3
Order By: Relevance
“…18 We can also learn from the causes evoked in studies on Black and White disparities. 48 Black individuals are more likely than white individuals to have a defeatist attitude toward medical illness, to experience stigma, fear and denial related to a cancer diagnosis, to mistrust the healthcare system, to have misperceptions about cancer and treatment benefits, to miss their medical visits and to be less participatory. Medical professionals may also have more difficulty to communicate, to present treatment enthusiastically, to provide care of high quality to black or low SES patients.…”
Section: Discussionmentioning
confidence: 99%
“…18 We can also learn from the causes evoked in studies on Black and White disparities. 48 Black individuals are more likely than white individuals to have a defeatist attitude toward medical illness, to experience stigma, fear and denial related to a cancer diagnosis, to mistrust the healthcare system, to have misperceptions about cancer and treatment benefits, to miss their medical visits and to be less participatory. Medical professionals may also have more difficulty to communicate, to present treatment enthusiastically, to provide care of high quality to black or low SES patients.…”
Section: Discussionmentioning
confidence: 99%
“…Health disparities are an important public health concern with several studies documenting racial and socioeconomic disparities in screening, incidence, stage at diagnosis, and mortality 6,8,10,[14][15][16][17][18][19][20][21][22][23] . As physician recommendation is a key determinant of patients' acceptance of screening, adequate access may be an important contributor to disparity.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that older individuals with cancer are at risk for receiving less than optimal care [2][3][4]. In particular, several investigators have found that substantial percentages of older individuals with stage III (node-positive) colon cancer do not receive chemotherapy [5,6], and this is particularly marked among black elderly [5][6][7]. This is of great concern, because chemotherapy is associated with substantially better survival in stage III colon cancer [8][9][10][11][12][13], and the beneficial effects of chemotherapy are still apparent in older adults [8,14,15], at least up to age 80.…”
Section: Introductionmentioning
confidence: 99%
“…While there have been substantial numbers of studies of factors associated with less than definitive treatment of cancer [2][3][4][5]7], there have been few studies on factors associated with the appropriate evaluation of the newly diagnosed cancer patient. In this study we used the Surveillance Epidemiology and End Results (SEER)-Medicare linked database to examine factors associated with medical oncology consultation and the impact of such consultation on chemotherapy use.…”
Section: Introductionmentioning
confidence: 99%